Einige Ergebnisse und Aussichten der Erforschung schädlicher Insekten der landwirtschaftlichen Nutzpflanzen in der Georgischen SSR. - Kobachidze, David (Contributions to Entomology = Beiträge zur Entomologie, 1959)
There is given a report on the results and prospects of the investigations of insects injurious to cultivated plants in the Georgian SSR.